Somalia-Yemen links: refugees and returnees - Mohamud, M (Refugee Studies Centre, University of Oxford, 2016)
The strategies of Yemeni refugees in Somalia are extensively based on the social networks and cultural linkages that exist between the Horn of Africa and Yemen. Meanwhile, Somali refugees returning from Yemen need to find safer areas within Somalia.